(untitled) (Eurasian Journal of Ecology, 2023)
The process of adsorption of sulfates and residual chlorine, which are the main sources of drinking water pollution, was investigated in the work. The shell of plum seeds activated by a vapor-gas mixture was used as an adsorbent. The shell of plum seeds is pre-carbonized at a temperature of 20 to 800 ° C and activated in a stream of CO2 and H2O in a mass ratio of 90:10 at a temperature of 750-850 ° C. The adsorption characteristics of sulfates and residual chlorine were investigated. The fastest adsorption of sulfates occurred on the adsorbent at a concentration of 500 mg/l. The characteristics of the kinetics of activated carbon adsorption by residual chlorine are found. The dependence of the absorption capacity of chlorine by activated carbons on the equilibrium concentration in water is determined. Upon reaching 90 minutes, we observe adsorption values of the order of 99%. The influence of the water flow speed on the absorption of residual chlorine by activated carbon was determined, where the optimal factor of the regime, the water flow speed, was 0.0022 m/s. The influence of the water flow speed on the turbidity index in the source and purified water was determined, where the maximum degree of purification for the activated shell of plum pits occurred at the water flow speed of 0.0022 m/s. The analysis of the data obtained indicates a satisfactory adsorption capacity of the studied activated carbons from the shell of plum pits and a high degree of water purification. Key words: adsorption, activated carbon, sulfate, residual chlorine, water purification, drinking water, water supply.